In vitro Evaluation of Oxidative Stress Caused by Fine Particles (PM2.5) Exhausted from Heavy-Duty Vehicles Using Diesel/Biodiesel Blends under Real World Conditions - Jesus,Robson M. de (2018)
In this work, the redox activity of fine diesel/biodiesel particulate matter (PM2.5) was studied in order to approach its toxicity from reactive oxygen species, due to adverse effects it may cause to human health. The oxidative potential was measured by the dithiothreitol (DTT) assay in order to study the relative contribution of water-soluble transition metals, polycyclic aromatic compounds (PAH), nitro-PAH, and quinones. It was analyzed a total of 24 samples collected from primarily diesel/biodiesel-exhausted particles from buses. The rate concentrations of PM2.5 redox activity ranged 0.020-0.069 nmol min-1 μg-1, with median at 0.040 nmol min-1 μg-1 (on average, 0.042 ± 0.005 nmol min-1 μg-1 for morning, 0.033 ± 0.007 nmol min-1 μg-1 for afternoon and 0.045 ± 0.009 nmol min-1 μg-1 for night). The transition metals appear to dominate the DTT response, since they were responsible up to 89% of redox activity measured in the samples. Apparently, the metal fraction contained in PM2.5 demonstrated a greater ability to catalyze reactions that promote the formation of reactive oxygen species when compared to organic compounds. It was observed that the oxidative potential of PM2.5 particles emitted from diesel/biodiesel (B7) is similar to diesel-emitted particles.